ADMINISTRASI KURIKULUM PENDIDIKAN ISLAM DI SD AL-ITTIHADIYAH LAUT DENDANG - Aziz, Mursal; Sholeh, Asmar; Harahap, Sania Mar’i Adnanda; Purba, Wanda Amelia (Al-Rabwah, 2024)
Administration of the Islamic education curriculum is something that has an important role in achieving educational goals. The aim of this research is to describe the administration of the Islamic education curriculum at SD Al-Ittihadiyah Laut Dendang. The administration of the Islamic education curriculum at Al-Ittihadiyah Laut Dendang Elementary School includes learning aspects that are well covered and recorded, starting from monitoring, student attendance and attendance, monthly class reporting to identify student needs to evaluating grades to measure the academic progress of students at Al-Ittihadiyah Laut Dendang Elementary School. Priority on effective administration provides a strong foundation for improving the quality of learning. The curriculum not only provides direction for the learning process, but also creates a foundation for the formation of students' character and spiritual values. Effective administration in managing the curriculum ensures that all aspects of learning are covered well, from the development of students' psychomotor aspects to parent participation in supporting school programs. Implementation of the Islamic education curriculum at Al-Ittihadiyah Laut Dendang Elementary School by emphasizing integration of Tahfizh subjects, development of students' psychomotor aspects, parent participation, and flexibility in implementing the curriculum.